2004
DOI: 10.1007/s10512-005-0068-y
|View full text |Cite
|
Sign up to set email alerts
|

Possibility, admissability, and desirability of implementing pulsed stochastic regimes in boiling-water reactors with natural coolant circulation

Abstract: A one-dimensional integral momentum model for the boiling-water channel and the point kinetic equations are used to study the conditions and mechanisms for the appearance of temporary pulses of stochastic regimes and regimes with pulsed turbulence of the neutron field in water-moderated water-cooled boiling-water reactors with natural circulation of the coolant. These self-excited oscillatory regimes occur as a result of a negative steam effect of reactivity. They consist of the fact that neutron bursts with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Chaotic oscillations of the density and velocity of two-phase flow in boiling-water heated channels, including in the channels of boiling-water reactors, are investigated in [1][2][3][4][5][6][7][8][9][10].…”
Section: The Chaotic Dynamics Of Boiling-water Reactors Is Investigatmentioning
confidence: 99%
See 1 more Smart Citation
“…Chaotic oscillations of the density and velocity of two-phase flow in boiling-water heated channels, including in the channels of boiling-water reactors, are investigated in [1][2][3][4][5][6][7][8][9][10].…”
Section: The Chaotic Dynamics Of Boiling-water Reactors Is Investigatmentioning
confidence: 99%
“…The properties of the mappings and the bifurcation of their stationary points are investigated.Chaotic oscillations of the density and velocity of two-phase flow in boiling-water heated channels, including in the channels of boiling-water reactors, are investigated in [1][2][3][4][5][6][7][8][9][10].A very simplified model of a boiling-water reactor is studied in [1, 2]; the model uses point equations of kinetics and a system of three ordinary differential equations to describe thermohydraulic processes in a reactor and the density feedback on reactivity. It is shown that chaotic oscillations during which the sign of the coolant velocity in the boiling channel changes occur in the case of strong feedback on steam content with the parameters of the boiling channel deep in the region of instability occur in boiling-water reactors with natural and forced circulation of the coolant.…”
mentioning
confidence: 99%
“…Novel reactor designs which admit a large increase in the core size have been proposed. The numerical calculations performed of self-excited oscillations on the basis of distributed models of a reactor [5,6] have shown that the methods proposed in the present work can be used effectively to control the temporal and spatial-time pulsed chaos in water-moderated water-cooled boiling-water reactors and in reactors with gaseous nuclear fuel.…”
mentioning
confidence: 92%
“…It is shown in [4][5][6] that if a regime of temporal pulsed chaos arises in small reactors, then increasing the reactor dimensions leaving all other parameters unchanged results in the appearance of a regime with pulsed turbulence of the neutron field. In this regime, neutron pulses having random intensity and occurring in random time intervals appear in local regions, whose dimensions, shape, and arrangement in the core vary irregularly in time, of the reactor.…”
mentioning
confidence: 99%
See 1 more Smart Citation